Jnk1 and downstream signalling hubs regulate anxiety-like behaviours in a zebrafish larvae phenotypic screen - Hong, Ye; Sourander, Christel; Hackl, Benjamin; Patton, Jedidiah S.; John, Jismi; Paatero, Ilkka; Coffey, Eleanor (Springer Nature, 2025)
Current treatments for anxiety and depression show limited efficacy in many patients, indicating the need for further research into the underlying mechanisms. JNK1 has been shown to regulate anxiety- and depressive-like behaviours in mice, however the effectors downstream of JNK1 are not known. Here we compare the phosphoproteomes from wild-type and Jnk1-/- mouse brains and identify JNK1-regulated signalling hubs. We next employ a zebrafish (Danio rerio) larvae behavioural assay to identify an antidepressant- and anxiolytic-like (AA) phenotype based on 2759 measured stereotypic responses to clinically proven antidepressant and anxiolytic (AA) drugs. Employing machine learning, we classify an AA phenotype from extracted features measured during and after a startle battery in fish exposed to AA drugs. Using this classifier, we demonstrate that structurally independent JNK inhibitors replicate the AA phenotype with high accuracy, consistent with findings in mice. Furthermore, pharmacological targeting of JNK1-regulated signalling hubs identifies AKT, GSK-3, 14-3-3 ζ/ε and PKCε as downstream hubs that phenocopy clinically proven AA drugs. This study identifies AKT and related signalling molecules as mediators of JNK1-regulated antidepressant- and anxiolytic-like behaviours. Moreover, the assay shows promise for early phase screening of compounds with anti-stress-axis properties and for mode of action analysis.